INTERACTIVE VIDEOS AND THEIR INCIDENCE IN THE DEVELOPMENT OF LISTENING SKILL IN ENGLISH LANGUAGE IN EIGHTH GRADE AT "LUZ DEL CAMPO" EDUCATIONAL UNIT, EL CARMEN-MANABÍ, IN 2017-2018 SCHOOL PERIOD. - ANDRADE ROMÁN, ERIKA LICETH (2017)
THROUGH THE WORK RELATED TO THE INTERCTIVE VIDEOS IN THE SUBJECT OF ENGLISH TO DEVELOP THE ABILITY TO LISTEN TO THE ENGLISH LANGUAGE, IT SERVES AS A GREAT EDUCATIONAL SUPPORT FOR THE TEACHING OF A SECOND LANGUAGE, PROVIDING CERTAIN BENEFITS FOR ITS PROCESS. IN MIDDLE EDUCATION THESE KINDS OF TECHNOLOGICAL SYSTEMS PROVIDE MANY OPPORTUNITIES ADDRESSED TO TEACHERS AND EVEN MORE TO STUDENTS...